An Attempt to Polarize Human Neutrophils Toward N1 and N2 Phenotypes in vitro - Ohms, Mareike; Möller, Sonja; Laskay, Tamás (Frontiers in Immunology, 2020)
Neutrophils act as the first line of defense against invading pathogens. Although traditionally considered in context of their antimicrobial effector functions, the importance of tumor-associated neutrophils (TANs) in the development of cancer has become increasingly clear during the last decade. With regard to their high plasticity, neutrophils were shown to acquire an anti-tumorigenic N1 or a pro-tumorigenic N2 phenotype. Despite the urgent need to get a comprehensive understanding of the interaction of TANs with their tumor microenvironment, most studies still rely on murine tumor models. Here we present for the first time a polarization attempt to generate N1 and N2 neutrophils from primary human neutrophils in vitro. Our results underscore that N1-polarized neutrophils have a pro-inflammatory phenotype characterized among others by a higher level of intercellular adhesion molecule (ICAM)-1 and high secretion of interferon (IFN)γ-induced protein 10 (IP-10)/C-X-C motif chemokine 10 (CXCL10) and tumor necrosis factor (TNF). Further, we demonstrate that neutrophils incubated under a tumor-mimicking in vitro environment show a high cell surface expression of C-X-C motif chemokine receptor 2 (CXCR2) and secrete high levels of interleukin (IL)-8. These findings suggest that it is feasible to polarize blood-derived primary human neutrophils toward N1- and N2-like phenotypes in vitro. Further, we hypothesized that the presence of anti-inflammatory neutrophil phenotype is not a phenomenon limited to cancer but also occurs when neutrophils are infected with intracellular pathogens. Indeed, our findings indicate that N2-polarized neutrophils exert a markedly decreased capacity to kill the protozoan parasite Leishmania donovani and therefore permit parasite persistence.